Water use efficiency of irrigated and rainfed crops of great importance in Serbia - Rodić-Trifunović Slađana; Stričević Ružica; Đurović Nevenka (Agroznanje, 2014)
As natural water supply rarely meets crop water requirements, irrigation has a great role in yield assurance in quantity and quantity. Irrigation could be economically justified if water use efficiency (WUE) is fulfilled. Therefore, the aim of this work was to determine WUE of irrigated and rainfed crops grown in Serbia. The analysis of crop water consumption and obtained yield was based on data collected from various scientific publications. Irrigation effect differed by years, but not strictly due to rainfall amount and occurrence. The yield of some crops strongly depends on available soil moisture such as alfalfa, fodder sorghum, maize and soybean with clear relationship, whereas of some crops such relation cannot be found. It indicates that WUE also depends on some other factors, such as extreme temperatures, frost, hail, nutrient supply and plant health, as well.